The Effect of some stress factors on the genetic stability of the sugar cane Saccharum officinarum L. in vitro - alaradi, haleemah; AbbasI, Muayad; Jasim, Abbas (Iraqi Journal of Aquaculture, 2024)
The current study was conducted in the tissue culture laboratory of the Marine science Center / University of Basrah. In order to increase the salt tolerance of two varieties of sugar cane, namely CO331and CP72-2086, the effect of the overlap between three levels of salinity (0,120 and 150 mmol) was studied with four doses of radiation (0,10,20,30 Gy) using gamma rays, The effect of the pretreatment with Ethyl Methane Sulfonate (EMS) for a period of (2.5 hours) on the salt tolerance of sugarcane callus was studied by cultivating callus treated with this compound in saline media containing the lethal dose (180 mmol) and higher than it (200 mmol). In addition to the control treatment, the results showed The differentiation of the plants from the callus that was exposed to different treatments resulted in plants with genetic variation when compared with the parent plant using the RAPD technique and four random primers. This variation ranged from 52.63% using the OPA-01 primer to 67.85% using the OPH-04 primer in cultivar CO331.While the genetic variation of cultivar CP72-2086 ranged from 29.41% using the primer OPA-01 to 69.23% using the primer OPH-04.